NILAI-NILAI PENGHORMATAN TERHADAP LELUHUR DALAM TRADISI NYOBENG MASYARAKAT ADAT DAYAK BIDAYUH MENURUT PERSPEKTIF EMMANUEL LEVINAS - Andi, Andi Prayoga; Kardy (JURNAL ILMU BUDAYA, 2023)
The Nyobeng tradition is a tradition that has important values for the civilization of the Life of the Bidayuh Dayak tribe. This tradition arose because it was motivated by the many rituals that became the custom of the community to honor what their ancestors had done in ancient times. For the Bidayuh Dayak tribe, honoring the merits of the ancestors is a noble deed and must be maintained and continued for generations. The way to honor the merits of these ancestors is the Bidayuh Dayak tribe to carry out a custom known as "Nyobeng". Nyobeng is not only celebrated casually, there are several series of events that must be included in the event, namely the "Ngayau" dance and the "Sabek'n Apa'k" dance. With regard to tradition, Emmanuel Levinas revealed that tradition must be based on the sensitivity of a person who is able to build ethical relationships between one another.